Peran Kejaksaan Republik Indonesia Dalam Penyelesaian Penanganan Perkara Tindak Pidana Penyalahgunaan Narkotika Melalui Rehabilitiasi - Ayni Suwarni Herry; Bima Guntara; Pendi Ahmad (Departement of Mathematics Education, 2023)
Narcotics are substances or drugs that are very useful and necessary for the treatment of certain diseases. However, if it is misused or used not in accordance with medical standards, it can have very detrimental consequences for individuals or society, especially the younger generation. This will be more detrimental if accompanied by the abuse and illicit traffic of Narcotics which can result in greater danger to the nation's life and cultural values which will ultimately weaken national security. The problem in this thesis is what is the role of the Attorney General's Office of the Republic of Indonesia in solving the handling of cases of criminal acts of narcotics abuse through rehabilitation. What is the scope of the Attorney General's Guidelines 18/2021 concerning Completion of Handling Cases Narcotics Abuse Crime Through Rehabilitation with a Restorative Justice Approach as the Implementation of the Prosecutor's Dominus Litis Principle. The research method used is empirical juridical research by conducting field research and library research. Primary data obtained from interviews with Kasi Wil I Sub Directorate. While secondary data obtained from the literature and books related to the problems that the author examined. The data obtained both primary and secondary were analyzed qualitatively. The results of the research show that the role of the Public Prosecutor's Office of the Republic of Indonesia in solving the handling of cases of criminal acts of narcotics abuse through rehabilitation is carried out through optimizing rehabilitation institutions. Prosecutors as case controllers based on the principle of dominus litis can carry out settlements of cases of criminal acts of narcotics abuse through rehabilitation at the prosecution stage.